From Competence Curriculum Design to Assessment and Certification of Achievement: two empirical models for TEFL - Capperucci, Davide (Studi sulla Formazione/Open Journal of Education, 2019)
Both the national and international literature identifies the development of design and assessment competences as a fundamental component in the professionalization of primary school teachers. This paper considers theoretical and methodological aspects of EFL curriculum design as it is addressed in Italy. Two empirical models are discussed: (i) a competence design model called the CUD Mod., based on the ‘competence unit’, and (ii) a model for achievement assessment and certification called ARCA. Both models were tested in action-research projects carried out in first-cycle schools in Tuscany. The contribution reflects on the experience which might also benefit other school contexts.